Production of greenhouse‐grown biocrust mosses and associated cyanobacteria to rehabilitate dryland soil function. Issue 3 (26th November 2015) - Antoninka, Anita; Bowker, Matthew A.; Reed, Sasha C.; Doherty, Kyle
Abstract : Mosses are an often‐overlooked component of dryland ecosystems, yet they are common members of biological soil crust communities (biocrusts) and provide key ecosystem services, including soil stabilization, water retention, carbon fixation, and housing of N2 fixing cyanobacteria. Mosses are able to survive long dry periods, respond rapidly to precipitation, and reproduce vegetatively. With these qualities, dryland mosses have the potential to be an excellent dryland restoration material. Unfortunately, dryland mosses are often slow growing in nature, and ex situ cultivation methods are needed to enhance their utility. Our goal was to determine how to rapidly produce, vegetatively, Syntrichia caninervis and S. ruralis, common and abundant moss species in drylands of North America and elsewhere, in a greenhouse. We manipulated the length of hydration on a weekly schedule (5, 4, 3, or 2 days continuous hydration per week), crossed with fertilization (once at the beginning, monthly, biweekly, or not at all). Moss biomass increased sixfold for both species in 4 months, an increase that would require years under dryland field conditions. Both moss species preferred short hydration and monthly fertilizer. Remarkably, we also unintentionally cultured a variety of other important biocrust organisms, including cyanobacteria and lichens. In only 6 months, we produced functionally mature biocrusts, as evidenced by high productivity and ecosystem‐relevant levels of N2 fixation. Our results suggest that biocrust mosses might be the ideal candidate for biocrust cultivation for restoration purposes. With optimization, these methods are the first step in developing a moss‐based biocrust rehabilitation technology.